(untitled) (gjstudies, 2026)
This research introduces a novel, cross-disciplinary framework that reconceptualizes the role of Management Accounting Information (MAI) in strategic decisionmaking by integrating principles from complex adaptive systems theory, information foraging theory from cognitive science, and network analysis. Moving beyondthe traditional, static view of MAI as a provider of historical financial data foroperational control, this paper posits that MAI systems must be designed as dynamic, anticipatory information ecosystems to effectively support strategic agilityin volatile environments. The core methodological innovation is the Strategic Information Resonance (SIR) model, which evaluates MAI not by its accuracy alone,but by its capacity to generate strategic insights through properties such as information diversity, connectivity, feedback latency, and scenario affordance. Wedevelop and apply a multi-method simulation employing agent-based modeling torepresent decision-makers interacting with different MAI system architectures under conditions of market turbulence. Our results demonstrate that MAI systemsoptimized for traditional variance reporting perform poorly in strategic contexts,often leading to decision paralysis or myopic reinforcement of past strategies. Incontrast, MAI systems designed using the SIR principles—particularly those emphasizing weak-signal detection and heterogeneous information synthesis—enableorganizations to identify emergent opportunities and threats 37% faster and with42% greater adaptive accuracy. The findings challenge the prevailing cost-benefitparadigm in accounting information system design, arguing for an investment in’strategic information infrastructure’ that treats MAI as a generator of strategicoptions rather than merely a recorder of financial consequences. This represents afundamental shift from accounting for strategy to accounting as a strategic capability.